2007
DOI: 10.1074/jbc.m707090200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Pepsin A Processing of Sonic Hedgehog in Parietal Cells Precedes Gastric Atrophy and Transformation

Abstract: Sonic hedgehog (Shh) is not only essential to the development of the gastrointestinal tract, but is also necessary to maintain the characteristic acid-secreting phenotype of the adult stomach. Gastrin is the only hormone capable of stimulating gastric acid and is thus required to maintain functional parietal cells. We have shown previously that gastrin-null mice display gastric atrophy and metaplasia prior to progression to distal, intestinaltype gastric cancer. Because reduced levels of Shh peptide correlate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 49 publications
5
92
0
1
Order By: Relevance
“…Although it has been shown by a number of laboratories that Shh is expressed and secreted from parietal cells (18,21,24), protein expression in the pit cells is unclear. One study has detected Shh expression in the pit region of Mongolian gerbils by using in situ hybridization (19), but in the mouse stomach there is conflicting data.…”
Section: Sonic Hedgehog Expression and Secretion From The Gastric Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been shown by a number of laboratories that Shh is expressed and secreted from parietal cells (18,21,24), protein expression in the pit cells is unclear. One study has detected Shh expression in the pit region of Mongolian gerbils by using in situ hybridization (19), but in the mouse stomach there is conflicting data.…”
Section: Sonic Hedgehog Expression and Secretion From The Gastric Mucosamentioning
confidence: 99%
“…Recently, we have found that in the stomach Shh processing occurs via a hormonally regulated and acid-dependent mechanism (24). In addition to regulating acid secretion, gastrin acts as a growth factor for the gastric mucosa.…”
Section: Sonic Hedgehog Processing In the Mammalian Stomachmentioning
confidence: 99%
“…A loss of gastric tissue homeostasis resulting in Correa sequence is associated with the impairment of Sonic Hedgehog (Shh) within the acidsecreting glands in atrophic gastritis and intestinal metaplasia [87,88]. The loss of parietal cells and a higher luminal pH associated with H. pylori chronic infection decreases Shh signaling, essential for restitution of damaged gastric mucosa from SCs [88,89]. However, loss of Shh alone is not sufficient to cause parietal cell atrophy and trigger GC [90].…”
Section: Hedgehog Pathwaymentioning
confidence: 99%
“…Recently, with the development of a mouse model expressing a parietal cell-specific Shh deletion, the function of this protein in adult stomach has been better clarified (Xiao et al, 2010). Shh ligand is expressed as a 45-kDa precursor that is cleaved autocatalytically to yield a 19kDa amino terminal fragment, that contains all the signaling functions and a 26-kDa www.intechopen.com carboxy-terminal fragment (ShhC), that acts as a cholesterol transferase (Goetz et al, 2006;Zavros et al, 2007). This activation process depends on the acid-activated protease pepsin A. Gastrin increases acid secretion in parietal cells leading to conversion of pepsinogen A to pepsin A, mediating Shh processing (Zavros et al, 2007).…”
Section: Hedgehog Pathwaymentioning
confidence: 99%
“…Shh ligand is expressed as a 45-kDa precursor that is cleaved autocatalytically to yield a 19kDa amino terminal fragment, that contains all the signaling functions and a 26-kDa www.intechopen.com carboxy-terminal fragment (ShhC), that acts as a cholesterol transferase (Goetz et al, 2006;Zavros et al, 2007). This activation process depends on the acid-activated protease pepsin A. Gastrin increases acid secretion in parietal cells leading to conversion of pepsinogen A to pepsin A, mediating Shh processing (Zavros et al, 2007). In the stomach, Shh binds directly to Ptch receptor but not to Smo being the activity of Smo controlled indirectly by Ptch (Figure 3).…”
Section: Hedgehog Pathwaymentioning
confidence: 99%